2020
DOI: 10.1021/acs.jafc.0c05233
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of a Sigma Glutathione S-Transferase CpGSTs2 Involved in λ-Cyhalothrin Resistance in the Codling Moth Cydia pomonella

Abstract: The codling moth, Cydia pomonella (L.), is a quarantine pest of global significance impacting pome fruits and walnuts. It has evolved resistance to many commonly used insecticides including λ-cyhalothrin. Glutathione S-transferases (GSTs) are multifunctional enzymes playing a crucial role in the detoxification of insecticides in insects. However, the role of specific GST gene in λ-cyhalothrin resistance in C. pomonella is unclear. In this study, we identified three sigma-class genes (CpGSTs1, CpGSTs2, and CpGS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 44 publications
(117 reference statements)
1
22
0
Order By: Relevance
“…18,39 Specifically, the midgut is the largest detoxification and metabolic tissue, whereas the fat body and Malpighian tubules are important organs for the absorption, storage, and excretion of xenobiotics and thus play an important role in detoxification. 16,17 In this study, 12 CpGSTs are expressed mainly in the midgut, 2 genes are expressed at the highest levels in the fat body, and 5 genes are predominantly expressed in Malpighian tubules. These results are consistent with previous reports on P. xylostella, B. mori, N. lugens, and B. dorsalis, which showed high expression levels of partial GST genes in detoxification-related tissues.…”
Section: ■ Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…18,39 Specifically, the midgut is the largest detoxification and metabolic tissue, whereas the fat body and Malpighian tubules are important organs for the absorption, storage, and excretion of xenobiotics and thus play an important role in detoxification. 16,17 In this study, 12 CpGSTs are expressed mainly in the midgut, 2 genes are expressed at the highest levels in the fat body, and 5 genes are predominantly expressed in Malpighian tubules. These results are consistent with previous reports on P. xylostella, B. mori, N. lugens, and B. dorsalis, which showed high expression levels of partial GST genes in detoxification-related tissues.…”
Section: ■ Discussionmentioning
confidence: 64%
“…A susceptible strain (SS) of C. pomonella was maintained in the laboratory for more than 50 generations without exposure to any insecticides. 16 A field population (ZW_R), which has developed a moderate (16.97-fold) level of resistance to lambda-cyhalothrin, 15 and its resistant regression population ZW_S (1.53-fold) 17 were used in this study. A detailed description of the feeding method has been previously described by Wang et al 13 Technical-grade (purity >98%) lambda-cyhalothrin was purchased from Aladdin Reagent (Shanghai, China) and 1-chloro-2,4-dinitrobenzene (CDNB, purity ≥99%) was obtained from Sigma-Aldrich (Shanghai, China).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA interference-mediated knockdown of CYP6DC1 signi cantly increased the sensitivity of resistant strain to acetamiprid 54 . mRNA level of GSTs2 was signi cantly higher in a eld resistance population in Cydia pomonella, and further metabolic assays indicated that λ-cyhalothrin could be depleted by recombinant GSTs2 55 . Although the number of highly expressed detoxi cation enzyme genes in winged M. dirhodum is much less than that of winged individuals, several of these genes have also been con rm to be important in insecticide resistance.…”
Section: Detoxi Cation Genes Differentially Expressed Between Winged ...mentioning
confidence: 93%
“…13 Epsilon and delta classes are considered to be specific in insects and are reported to metabolize insecticides and confer resistance to many classes of insecticides. 14,15 GSTe4 is up-regulated in resistant populations of A. gambiae and Anopheles arabiensis, and plays a role in pyrethroid metabolism by insecticide sequestration. 16 In Cydia pomonella, lambda-cyhalothrin can induce the expression of CpGSTd1 and CpGSTd3, and is metabolized by the recombinant protein of CpGSTd1, CpGSTd3 and CpGSTe3.…”
Section: Introductionmentioning
confidence: 99%